Pengaruh Metode Problem Solving dalam Meningkatkan Berpikir Kritis Peserta Didik pada Mata Pelajaran PAI - Nazaiqa Ikhwannul Haq; Dede Supendi; Saepul Mukti (Moral : Jurnal kajian Pendidikan Islam, 2025)
In the era of globalization and the Industrial Revolution 4.0 in the 21st century, critical thinking skills become a crucial competence that students must master. However, based on preliminary observations and previous research, it was found that many high school students lacked the ability to think critically in the learning process, especially in Islamic Education subjects. This research aims to find out how the problem solving method affects the critical thinking skills of students in PAI subjects in class XI of Purwakarta State High School 3. This research uses a quantitative approach with the one group pre-test post-test pre-experimental method. The research results showed that the average pre-test and post-test scores increased by 29.4%, the wilxocon hypothesis test also showed a significant influence from the application of problem solving methods in improving students' critical thinking skills. However, the results of the N-Gain calculation show that the effectiveness of the increase is in a low category. This indicates that although the problem solving method has a significant impact, the magnitude of the impact or effectiveness is still not optimal.